The Relationship of the Duration of Social Media Instagram Usage and Student's Eating Behavior in University of Sumatera Utara, 2019 - Selvi Karmila; Evawany Y. Aritonang; Etti Sudaryati (Britain International for Academic Research (BIAR) Publisher, 2020)
The development of technology and culinary tourism has led to the high enthusiasm of social media users to bring up various Instagram culinary accounts that promote food. Food recommendations provided by food bloggers can be information, references in choosing food. The average duration of social media usage in Indonesia in 2018 is 3 hours 23 minutes a day. Exposure to food information on Social media instagram raises problems in choosing foods for students who are not concerned with the nutritional content of food that causes changes in eating behavior. This study aims to analyze the relationship of the duration of social media Instagram usage and student's eating behavior in University of Sumatera Utara. This study was an observational study using a cross-sectional design. The population in this study were undergraduate students at University of Sumatera Utara, with sample of 344 students. The data collection tool uses a questionnaire. Bivariate analysis using the Chi-Square statistical test. The results showed that the duration of social media Instagram usage among respondents was categorized high (≥3 hours / day) as much as 55.8 percent. Bivariate analysis shows that there is a significant relationship of the duration of social media Instagram and eating behavior (p <0.05). Students are expected to be able to limit themselves in using social media Instagram and are advised to consume balanced food. We recommend that the media such as Instagram culinary accounts can insert health messages as a food reference.